Improved estimation of global solar radiation over rugged terrains by the disaggregation of Satellite Applications Facility on Land Surface Analysis data (LSA SAF). (24th August 2020) - Fibbi, Luca; Maselli, Fabio; Pieri, Maurizio
Abstract: This paper presents a new method to predict global solar radiation over irregular terrain, named Estimation of global solar RADiation (ERAD). The method is based on the disaggregation of Satellite Applications Facility on Land Surface Analysis (LSA SAF) data using a digital elevation model and is applied in Italy with a time step of 1 min and a spatial resolution of 200 m. A quantitative assessment of ERAD is performed in comparison with three other standard methods (Mountain Microclimate Simulation Model [MTCLIM], LSA SAF and Copernicus Atmosphere Monitoring Service [CAMS]) using measurements taken in 43 stations located in Italy or in the surrounding countries, in the years 2005–2016. Such assessment concerns the irradiance incoming on a horizontal surface, which is measured by ground radiation sensors and is summarized by means of four accuracy statistics (i.e. mean absolute error [MAE], root mean square error [RMSE], coefficient of determination [ R 2 ] and mean bias error [MBE]). Overall, the average daily global solar radiation estimates obtained by ERAD have RMSE and R 2 about 25 W·m −2 and 0.943, respectively. These statistics are similar to those of LSA SAF and better than those of CAMS and, above all, MTCLIM. The bias analysis by elevation ranges shows a slight ERAD overestimation over plains and hills and a slight underestimation over mountains. An additional qualitative assessment shows how the ERAD radiation estimates are more spatially detailed than those of the other methods and are redistributed on inclined surfaces consistently with expectations. Abstract : This paper presents a new method to predict global solar radiation over irregular terrain, named Estimation of global solar RADiation (ERAD). Solar radiation is downscaled over Italy using a digital elevation model at 200 m and a time step of 1 min. ERAD is assessed in comparison with three other standard methods (MTCLIM, LSA SAF and CAMS) versus observations taken in 43 weather stations from 2005 to 2016. The daily global solar radiation estimates obtained by ERAD have root mean square error and R 2 about 25 W·m −2 and 0.943, respectively.